Pengaruh Metode Solmisasi terhadap Kemampuan Bermusik melalui Pianika pada Siswa Disabilitas Netra - Jemain, Eduardus Lindi; Sugihartatik, Sugihartatik; Yaum, Lailil Aflahkul (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of the solmization method in learning pianica on the musical abilities of students with visual impairments at SLB Branjangan Jember. This study used the Single Subject Research (SSR) method with an A-B design. The baseline phase (A) was conducted for five sessions to observe students' initial musical abilities without treatment. Furthermore, in the intervention phase (B), which lasted for seven sessions, students were given learning using pianica with the solmization method. Data were analyzed to see changes in students' abilities between the two phases. The results showed that students experienced a significant increase in musical skills after the intervention. In the baseline phase, students had difficulty recognizing and playing notes correctly. However, students could identify and play notes better after using the pianica with the solmization approach. In conclusion, applying solmization in pianica learning can be an effective method for students with visual impairments to improve their musical abilities. This study contributes to more inclusive music learning for students with visual impairments. By implementing solmization and using the pianica, students can learn music more easily and in a structured manner according to their needs.   Keywords: Solmization Method, Musical Ability, Pianica, Visual Disability